A characterization of the category FCS - Tiwari H.; Srivastava R. (My University, 2025)
Srivastava et al. (J Fuzzy Math 2:525–534, 1994) introduced the notion of a fuzzy closure space and studied the category FCS of fuzzy closure spaces and fuzzy closure preserving maps. In this article, we have introduced the Sierpinski fuzzy closure space and proved that it is a Sierpinski object in the category FCS. Further, a characterization (up to an isomorphism) of the category FCS is given, with the help of the Sierpinski fuzzy closure space. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.